(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: in Uruguay, between December 2020 and March 2021, there was a steady increase in community transmission of the SARS-CoV-2 virus when it reached a Harvard IP7 index of 24.07. Considering the negative consequences of closing down schools and the fact that, unlike adults, children are less vulnerable and transmit the infection less, it was decided to resume partial school attendance, despite the epidemiological situation. It is necessary to analyze the characteristics of the transmission in these centers to evaluate the impact of the mitigation measures. Objective: describe the characteristics of the transmission of SARS CoV-2 infection in several children at risk of exposure at their schools and assisted by a private health provider. Methodology: descriptive, retrospective study of children under 15 years of age with SARS-CoV-2 infection at risk exposure at educational centers in March 2021. Clinical variables (age, sex, clinical manifestations, evolution), characteristics of exposure (index case, compliance with physical distancing measures, wear of face masks) and secondary cases. The data source was health medical records and a supplementary telephone survey to the mother, father and/or guardian. Results: 198 of the 804 children under 15 years of age with SARS-CoV-2 infection (24.6%) presented risk exposure at their educational centers. Average age 8 years, 51% female. 53% were asymptomatic and 47% had mild symptoms. None required hospitalization or presented post-infectious complications at the time of communication. The index case was an adult in 64% and a child in 36%. They reported having complied with physical distance restrictions 45% and use of a mask 60%. In 45% secondary cases occurred at home, one of them died (65 years old, type 2 diabetes mellitus). Conclusions: in this scenario with high rates of community circulation, more than a quarter of the children in this series acquired the infection in an educational center, mostly from an adult. Although most of the children were asymptomatic or developed mild forms of the disease, a significant proportion continued the chain of transmission and generated secondary intradomiciliary cases. It is possible that lack of compliance with physical distancing protocols and with the use of the mask, added to the circulation of gamma VOC (P1) in the early stages of the vaccination campaign and can explain these findings. Analysis of the transmission dynamics is essential to optimize pandemic mitigation measures.